2018
DOI: 10.1177/1477760618798274
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable molding process for new rubber products from tire recycling

Abstract: A new technology has been developed to produce large-size rubber products by molding ground tire rubber (GTR) without using any binder or other substance. GTR is compression molded at high pressure and temperature to achieve an optimal particle adhesion. Large-size tiles (1 m2) with thickness up to 50 mm have been molded without cracks or other damages. In this study, for the first time, energy consumption has been precisely estimated in different phases of the process cycle and discussed together with mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…High temperature and pressure also enhanced the sintering of GTR particles without using additional additives [ 41 , 42 ]. This is related to the combined effects of the devulcanization, degradation, and secondary vulcanization (revulcanization) of GTR (or GTR with NBR) supported by free radicals’ reactions.…”
Section: Resultsmentioning
confidence: 99%
“…High temperature and pressure also enhanced the sintering of GTR particles without using additional additives [ 41 , 42 ]. This is related to the combined effects of the devulcanization, degradation, and secondary vulcanization (revulcanization) of GTR (or GTR with NBR) supported by free radicals’ reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The simpler methods are their use as inert filler for constructions [5,6] and as road asphalt [7] or for the direct production of raw materials such as rubber [8][9][10] and textiles [11]. Alternatively, thermochemical routes are cost-effective approaches for end-life tires treatment avoiding the complexity of alternative management routes [12] such their conversion through pyrolytic techniques [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum average stress and strains are 2.6 MPa and 330%, respectively. Even if these values are lower than virgin rubber compounds, they are significantly higher than previously adopted reclaimed compounds for RU-FREIs [8,12]. A tear resistance of 6.94 N/mm was measured, which is lightly lower than the minimum requirements, i.e.8 N/mm [20].…”
Section: Novel Rubber Compound Investigationmentioning
confidence: 90%
“…Another method to obtain a 100% recycled rubber material consists in compression moulding of rubber granules at elevated temperature and pressure, necessary to break the crosslink bond, without the addition of any binder [9][10][11]. This material exhibits good mechanical properties and high density [12]. Some studies have shown the possibility of using rubber pads to produce recycled rubber isolators reinforced with carbon fibres (RU-FREI) avoiding the vulcanization process [13].…”
Section: Introductionmentioning
confidence: 99%